Application of Lattice-Gas Model to the Simulation of Complex Economical Systems - Juwono, Tjipto (Surya University, 2015)
The lattice-gas model simulations are being used to reproduce the collective behavior of complex economic systems. By correlating different manifestation of the collective behaviors to the parameter changes in the simulation, we identify the underlying mechanism of the various manifestation of the collective behavior. The standard growth model is reproduced by the model with non-interacting agent. As we introduce interacting agents, the growth model departs from the standard.  Using cluster labeling algorithm we obtain number density histograms and diversity to explain the underlying mechanism of the growth dynamics.